Cultivating leaders for primary health care: A revised approach for transformative development - Klaus B. von Pressentin; Angela de Sá; Paddy Pampallis; Tasleem Ras (AOSIS, 2024)
Family physicians require leadership skills to strengthen team-based primary care services. Interviews with South African district managers confirmed the need to develop leadership skills in family physicians. The updated national programmatic learning outcomes for South African family physician training were published in 2021. They sparked the need for curriculum renewal at the University of Cape Town's Division of Family Medicine. A review of the leadership and governance module during registrar training showed that the sessions were perceived to be content heavy with insufficient opportunities for reflection. Following a series of stakeholder engagements, the module convenors co-designed a revised module that was blueprinted on the updated learning outcomes. The module incorporates a group coaching style, facilitating learning through reflection on one's experiences. The revised module was implemented in 2022. It aims to provide a transformative learning experience centred on students' perceptions of themselves as leaders, as well as professional identity formation and resilience building. This short report describes preliminary insights from the revised module's developmental phase and forms part of an ongoing iterative evaluation process. Contribution: Family physicians should lead across all their defined roles. Formal and informal learning opportunities are needed to facilitate their growth as leaders and help them to meet the health needs of communities served by an evolving health care system. This short report describes an example of a revised postgraduate module on leadership and governance, which may be of value to clinician educators and academic departments exploring innovative methods for the African region.